Arterial blood gases predict long-term prognosis in stage I non-small cell lung cancer patients. Issue 1 (December 2016) - Mizuguchi, Shinjiro; Iwata, Takashi; Izumi, Nobuhiro; Tsukioka, Takuma; Hanada, Shoji; Komatsu, Hiroaki; Nishiyama, Noritoshi
Abstract Background Preoperative hypercapnia and hypoxemia are reportedly risk factors for postoperative complications. This study aimed to establish the long-term survival risk associated with abnormal preoperative arterial blood gases (ABGs) in patients with non-small cell lung cancer (NSCLC). Methods This study involved 414 patients with stage I NSCLC who underwent lobectomy/bilobectomy with mediastinal lymph node dissection. The patients were divided into groups with normal (n  = 269) and abnormal (n  = 145) ABGs. Results The patients in the normal ABG group (median age 67 years) were significantly younger than those in the abnormal ABG group (median age 70 years). There were no significant differences between the groups in gender, performance status, pathological stage, histology, postoperative complications, or preoperative comorbidity, except for chronic obstructive pulmonary disease/pulmonary fibrosis. The 3-, 5- and 10-year survival rates in the normal and abnormal ABG groups were 87, 77 and 56, and 78 , 63 and 42 %, respectively (p  = 0.006). According to multivariate analysis, age, gender, performance status, non-adenocarcinoma, differentiation of resected tumor, pathological stage, any prior tumor and abnormal ABGs (risk ratio, 1.61) were independent prognostic factors. Conclusions Abnormal ABGs predict long-term survival risk in patients with NSCLC, which is important for planning therapeutic strategies.